2021
DOI: 10.1088/1361-648x/ac1822
|View full text |Cite
|
Sign up to set email alerts
|

The effect of finite-temperature and anharmonic lattice dynamics on the thermal conductivity of ZrS2 monolayer: self-consistent phonon calculations

Abstract: Two-dimensional (2D) ZrS2 monolayer (ML) has emerged as a promising candidate for thermoelectric (TE) device applications due to its high TE figure of merit, which is mainly contributed by its inherently low lattice thermal conductivity. However, the inadequate understanding of the lattice anharmonicity and its effect on the phonon dispersion and lattice thermal conductivity can be misleading in revealing the actual significance of ZrS2 ML in thermoelectrics. Here we investigated the temperature-dependent phon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In previous studies on the lattice thermal conductivity of 2D materials, SCPH calculations were only applied to study the thermal conductivity of ferroelectric systems in different phases or improve the accuracy of calculations. 20,51 This finding shows the importance of SCPH calculations in the study on the thermal conductivity of 2D materials. By calculating the three-phonon scattering rates, as shown in Figure 2c, one can see that the three-phonon scattering rates do not vary monotonously with strain, which contributes to the oscillatory decrease of the calculated κ l 3 .…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In previous studies on the lattice thermal conductivity of 2D materials, SCPH calculations were only applied to study the thermal conductivity of ferroelectric systems in different phases or improve the accuracy of calculations. 20,51 This finding shows the importance of SCPH calculations in the study on the thermal conductivity of 2D materials. By calculating the three-phonon scattering rates, as shown in Figure 2c, one can see that the three-phonon scattering rates do not vary monotonously with strain, which contributes to the oscillatory decrease of the calculated κ l 3 .…”
mentioning
confidence: 72%
“…One can see in Figure b that the response of thermal conductivity to strain calculated by using the second-order IFCs without SCPH renormalization is consistent with the nonmonotonic behavior of previous studies on 2D materials. , However, the trend changes into oscillating descent behavior once involving the temperature effect calculated by using SCPH theory. In previous studies on the lattice thermal conductivity of 2D materials, SCPH calculations were only applied to study the thermal conductivity of ferroelectric systems in different phases or improve the accuracy of calculations. , This finding shows the importance of SCPH calculations in the study on the thermal conductivity of 2D materials. By calculating the three-phonon scattering rates, as shown in Figure c, one can see that the three-phonon scattering rates do not vary monotonously with strain, which contributes to the oscillatory decrease of the calculated κ l 3 .…”
mentioning
confidence: 99%
“…However, anharmonicity of ZrS 2 lattice can play a major role in this upshift with temperature. Recent calculations on anharmonicity of ZrS 2 phonons using self‐consistent phonons reveal a pronounced anharmonicity effect with increasing temperature, [ 44 ] which evidently can alter phonon dynamics with temperature. In addition, the dipolar coupling between Raman‐active A 1g phonon mode and infrared‐active phonons (A 2u (LO) and E u modes) due to the long‐range coulomb forces caused by charges on atoms can contribute to the observation of this anomalous upshift of A 1g mode and downshift of A 2u mode.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a thermal conductivity of 3.85 W mK À1 , which is higher than the value of classic BTE, but still significantly lower than those of other materials. 9 Theoretical studies have shown that these two materials have similar lattice structures and phonon dispersion curve structures, so it is speculated that they have similar physical properties. 10,11 In addition to the application environments of devices, strain engineering, as the simplest adjustment method, has been widely used in the regulation of the thermoelectric properties of two-dimensional materials.…”
Section: Introductionmentioning
confidence: 99%